Pattern of synonymous codon usage in three strains of human coxsackievirus - Tee, Sim-Hui (Sunway University, 2014)
The pattern of synonymous codon usage in organisms is not displayed in a random fashion. Some codons are used more frequently than the alternative synonymous codons. This phenomenon is found across species and across genes within a genome. This research investigated the patterns of synonymous codon usage in three strains of human coxsackievirus, using the bioinformatics approach. It was found that the studied strains exhibit a less biased synonymous codon usage pattern, which implies the low expressivity of the genes. Understanding of the patterns of synonymous codon usage is critical to the therapeutic strategies and drug designs to counteract the infection of human coxsackievirus.